Saint Anything a novel - Dessen, Sarah (New York, New York Viking, an imprint of Penguin Group (USA), 2015)
Sydney's charismatic older brother, Peyton, has always been the center of attention in the family but when he is sent to jail, Sydney struggles to find her place at home and the world until she meets the Chathams, including gentle, protective Mac, who makes her feel seen for the first time
1
Keywords: JUVENILE FICTION / Family / General (see also headings under Social Issues); JUVENILE FICTION / Love & Romance; JUVENILE FICTION / Social Issues / Friendship; Brothers and sisters -- Fiction; Dating (Social customs) -- Fiction; Family life -- Fiction; Family problems -- Fiction; Friendship -- Fiction; Self-perception -- Fiction